STRATEGI PEMBELAJARAN KESENIAN ULU AMBEK PADA MASA PANDEMI DI PARIAMAN - Yulinis Yulinis (Pascasarjana Institut Seni Indonesia Padang Panjang, 2022)
This article discusses the ulu ambek art learning strategy during the Covid-19 pandemic in Pariaman, which faces a new problem, namely the prohibition of gathering activities. This situation is certainly very risky for every cultural unit if it is not strong in defending itself. Ulu ambek art inevitably has to try to find alternatives to learning strategies to respond to the pandemic, one of which is to try online learning by utilizing digital technology media. The results of the analysis show that online learning strategies are difficult to apply to the ulu ambek. Because, the art of ulu ambek as an important part of Pariaman culture, holds the values and perceptions of the Pariaman people, especially the value of the leadership of the penghulu. Ulu ambek art is defined as a manifestation of the abstraction of the penghulu in Pariaman, including ideas, behaviors, and results of behavior. Both values and perceptions relate to the psychological aspects of ulu ambek supporters, which are important in directing their behavior, which are difficult to internalize through online learning strategies.Keywords: pandemic; strategy; learning; Pariaman; ulu ambek AbstrakTulisan ini membicarakan tentang strategi pembelajaran kesenian ulu ambek pada masa pandemi Covid-19 di Pariaman, yang menghadapi persoalan baru yaitu dilarangnya kegiatan berkumpul. Keadaan ini tentunya sangat berisiko bagi setiap unit kebudayaan jika tidak kuat dalam mempertahankan dirinya. Seni ulu ambek mau tidak mau harus berusaha untuk menemukan alternatif dari strategi pembelajaran guna menyikapi pandemi, salah satunya adalah mencoba pembelajaran daring dengan memanfaatkan media teknologi digital. Hasil analisis menunjukkan bahwa strategi pembelajaran daring sulit diterapkan atas ulu ambek. Sebab, seni ulu ambek sebagai bagian penting kebudayaan Pariaman, menyimpan nilai-nilai dan persepsi masyarakat Pariaman, terutama atas nilai kepemimpinan penghulu. Seni ulu ambek didefinisikan sebagai wujud dari abstraksi penghulu di Pariaman, mencakup gagasan, kelakuan, dan hasil kelakuan. Baik nilai-nilai maupun persepsi, berkaitan dengan aspek-aspek kejiwaan para pendukung ulu ambek, yang penting artinya dalam mengarahkan tingkah laku mereka, yang sulit diinternalisasikan melalui trategi pembelajaran daring.Kata Kunci: pandemi; strategi; pembelajaran; Pariaman; ulu ambek